2022
DOI: 10.1007/s11103-022-01319-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways mediate chloroplast singlet oxygen stress signaling

Abstract: Chloroplast singlet oxygen initiates multiple pathways to control chloroplast degradation, cell death, and nuclear gene expression.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 80 publications
5
24
0
Order By: Relevance
“…However, this necessitates that the plants be screened as adults after being selected for transgenesis. It has been previously shown that when grown as adults in cycling light conditions, fc2 mutants do initiate 1 O 2 signaling (Woodson et al, 2015, Lemke et al, 2021, Tano et al, 2023). However, fts suppressor mutants have mostly been characterized as seedlings and it is unclear how they behave as adults (a summary of published fts mutants and their seedling phenotypes can be found in Table S7) .…”
Section: Resultsmentioning
confidence: 99%
“…However, this necessitates that the plants be screened as adults after being selected for transgenesis. It has been previously shown that when grown as adults in cycling light conditions, fc2 mutants do initiate 1 O 2 signaling (Woodson et al, 2015, Lemke et al, 2021, Tano et al, 2023). However, fts suppressor mutants have mostly been characterized as seedlings and it is unclear how they behave as adults (a summary of published fts mutants and their seedling phenotypes can be found in Table S7) .…”
Section: Resultsmentioning
confidence: 99%
“…Here we report the cellular manifestations of osmotic stress in the root through the lens of singlet oxygen production. Most studies about singlet oxygen are confined to aerial organs where the creation of singlet oxygen through photodynamic processes occurs in high light or in mutant plants (Mattila et al, 2023; Tano et al, 2023; Zhang et al, 2023). In those cases, dysfunction of photosynthesis and the production of singlet oxygen generated chemical messengers were shown to dramatically effect plant physiology (Li and Kim, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lesion formation in acd2 may be distinct from EL-induced 1 O2 signaling, which involves both PUB4 and OXI1 in wt and ch1 mutants 11,24 .…”
Section: Main Textmentioning
confidence: 98%
“…However, it is not known if these mutants represent one or multiple chloroplast signaling pathways. To this end, we recently used a meta-analysis of previously published whole transcriptome data sets of the three mutants to determine if they regulate the same set of genes 24 due to generating the same 1 O 2 signal. We observed that they share a small core transcriptional response to 1 O 2 stress (36 genes), but maintain unique patterns.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation